How Blended Learning Influences Employee Performance:The ‎Mediating Role of Soft Skill Development And Knowledge Acquisition - Uddin, Maeen; Ahamed , Md. Rasel; Jakowan; Islam , Md. Rafiqul; Nahar , Maherun (International Journal of Accounting and Economics Studies, 2026)
Blended learning has become a crucial factor in corporate training, yet its precise pathway to ‎enhancing employee performance remains unexplored. This study investigates the indirect ‎mechanisms through which blended learning effectiveness (BLE) impacts employee ‎performance (EP), proposing soft skill development (SSD) and knowledge acquisition (KA) ‎as mediating variables. Data were collected from 150 employees with prior blended learning ‎experience. Structural equation modeling was deployed to test a parallel mediation model. ‎The results show that blended learning strongly and positively affects both soft ‎skill development and knowledge acquisition. However, it shows no significant direct effect ‎on employee performance. Instead, soft skill development and knowledge acquisition fully ‎mediate this relationship, serving as the mechanisms through which blended learning ‎translates into improved performance. The model exhibits a robust fit and explains a ‎significant portion of performance variance. The study posits that blended learning enhances ‎employee performance not directly, but by first building essential interpersonal competencies ‎and job-relevant understanding. These findings offer both theoretical clarity for training ‎models and practical guidance for designing impactful corporate learning programs‎.
Keywords: Blended Learning; Employee Performance; Knowledge Acquisition; Soft Skill Development; ‎Structural Equation Modeling